Anatomy of a conflict: deconstructing ontological fracture in Jammu and Kashmir - Khaniejo, Natallia (Nanyang Technological University, 2023)
This thesis undertakes a genealogical analysis of the constructed nature of the Kashmir ‘problem’ and attempts a denaturalization of the discourse that constructs the region into a conflict. Drawing on poststructuralist and postcolonial approaches, the thesis attempts to demonstrate that the Kashmir conflict did not emerge out of a void, but was instead constructed, and perpetuated through the language game of empires, and subsequently, nation states. While I’m not claiming that the region came into existence with the colonial empire, I do argue that the political unit (currently seen as a conflict), is one whose construction is rooted in colonial state-making. I further argue that as long as the region is continually seen through the lens of nation states and referred to through the language game of nations, it will continue to be a conflict arrested within the dyad of being either a victim or a threat.